EFEKTIVITAS PENDEKATAN COGNITIVE BEHAVIOR THERAPY (CBT) DALAM KONSELING KELOMPOK UNTUK MEREDUKSI INSECURITY PADA SISWA KELAS VII D SMP NEGERI 18 KOTA SURAKARTA TAHUN PELAJARAN 2025/2026 - Indah Megantara; Sri Suryanti, Hera Heru; Jawandi, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indah Megantara. THE EFFECTIVENESS OF THE COGNITIVE BEHAVIOR THERAPY (CBT) APPROACH IN GROUP COUNSELING TO REDUCE INSECURITY AMONG THE SEVENTH-GRADE D STUDENTS OF SMP NEGERI 18 SURAKARTA IN THE ACADEMIC YEAR 2025/2026. The aim of this research was to determine the effectiveness of the Cognitive Behavior Therapy (CBT) approach in group counseling services to reduce the level of insecurity among the seventh-grade D students of SMP Negeri 18 Surakarta in the Academic Year 2025/2026. The research method used was an experiment with a one group pretest-posttest design. The subjects of this study were 8 seventh-grade D students selected using purposive sampling technique. The research instrument was an insecurity questionnaire administered before and after the treatment. The treatment provided was group counseling services using the CBT approach conducted over three sessions. Data were analyzed using the Wilcoxon test with the assistance of the SPSS 25.0 program. The results of the data analysis using the Wilcoxon test showed an Asymp. Sig. (2-tailed) value of 0.011 < 0.05, thus Ho was rejected and Ha was accepted. This proved that there was a significant decrease in the level of insecurity among students after being given group counseling services using the CBT approach. Therefore, it could be concluded that the Cognitive Behavior Therapy (CBT) approach in group counseling is effective in reducing insecurity among seventh-grade D students at SMP Negeri 18 Surakarta in the Academic Year 2025/2026. This research is expected to contribute to guidance and counseling teachers in developing group counseling service programs to help students overcome insecurity issues. Keywords: Group Counseling, Cognitive Behavior Therapy (CBT) Approach, Insecurity